A bibliometric analysis of 47-years of research on public health in Peru - Moya Salazar, Jeel Junior (2023)
Objectives: To measure Peruvian scientific production on public health in Scopus database. Methods: Bibliometric study using advanced Scopus web search engine (https://www.scopus.com/search/ form.uri?display=advanced). The inclusion criteria were the publications of articles related to public health between 1973 and 2020. The equation was used as a strategy: TITLE-ABS-CLAVE (“public health”) AND AFFILCOUNTRY (Peru) AND (EXCLUDE (PUBYEAR, 2021) OR EXCLUDE (PUBYEAR, 2020)). SCImago journal & country rank was used to determine the impact factor (h-index) and the quartile of the journals identified. The analysis included in SPSS v24.0 included years of publication, institutions, h-index, list of authors with the most publications, publication types, and journals. Results: 903 articles published by 7.5±12.5 authors were included, showing that 74.5% were original articles written mainly in English (77.7%). The publications for the year 1973 and 2019 were 3 (0.3%) and 98 (10.9%), respectively. In addition, it was shown that the most productive institutions were the Universidad Peruana Cayetano Heredia (42.9%) and the Universidad Nacional Mayor de San Marcos (13.1%). The journal with the highest number of Peruvian publications was Revista Peruana de Medicina Experimental y Salud Pública (RPMESP) [Peruvian Journal of Experimental Medicine and Public Health (PJEMPH)] (17.5%) and PLoS ONE (2.88%). Conclusions: The present study showed in the magazines with the highest number of citations and therefore greater visualization, where Peruvian publications in this area were published, with this the future readers can take these magazines into consideration so that their publications have a greater visualization. In addition to this, the study shows the largest institutions that have a great impact on Peruvian publications in public health in Scopus, this invites researchers to analyze the research methodologies that these institutions follow in order to disclose them for reproduction in new entities interested in research.